Effect of energy-based devices on skin retraction in gynaecomastia in comparison to conventional techniques: a prospective observational study - Garg, Prince; Koudki, Rakesh; R., Ravi D. (International Surgery Journal, 2026)
Background: Gynecomastia is a common benign condition in males that often requires surgical correction to achieve satisfactory aesthetic outcomes. Power-assisted liposuction (PAL) is widely used; however, optimal skin retraction remains challenging. Methods: This prospective cohort study evaluated whether the addition of radiofrequency-assisted liposuction (RFAL) to PAL results in superior skin retraction compared with PAL alone in patients undergoing gynecomastia surgery. Results: A total of 32 patients were equally divided into PAL alone and RFAL+PAL groups. Baseline demographic characteristics and Simon’s grading were comparable between the groups. Both techniques resulted in progressive improvement in nipple–areola complex size and positioning over 6 months; however, the RFAL+PAL group demonstrated significantly greater reduction in NAC horizontal diameter and improved positioning (p<0.001). Conclusions: The addition of RFAL to PAL significantly enhances skin retraction and aesthetic outcomes in gynecomastia surgery, providing superior NAC reduction, improved alignment and sustained contour refinement compared with PAL alone.